Edukasi bermain online games secara sehat pada anak-anak usia sekolah dasar - Rahmawati, Aulia; Tutiasri, Ririn Puspita (University of Islam Malang, 2021)
Based on recent researches, there is an alarming rate of children addiction towards online games, from the mild ones to the heavy ones. These community empowerment activities focus upon the educational purposes for elementary school children in developing healthy games-online habits. Games online were chosen because they posed more risks in comparison to offline games since the anonymity in the virtual world. Initial interviews, FGDs and training were methods chosen and were continued with educational activities and advocacy. From the initial reviews, it was found that many school-aged children have their own gadgets and have their own social media accounts. It was also found that students spent 2 to 4 hours per day using their gadgets, mostly playing online games without parental supervision. This community empowerment act produces several recommendation and suggestions responding to these problems. Firstly, we recommend children to be open to their parents in regards of their online activities (including games they participate daily). Secondly, we recommend children not to engage in private conversation with strangers in virtual worlds. Thirdly, we also advocate children to produce creative contents instead of being passive consumers. Further advocacies and trainings are needed and will be organise after the school is safe and open after Covid-19 pandemic.